Problems of mini-pig breeding - K. S. Shatokhin (Вавиловский журнал генетики и селекции)
This article provides an overview of some problems of the breeding and reproduction of laboratory minipigs. The most obvious of these are the lack of centralized accounting of breeding groups, uniform selection standards for reproduction and evaluation of breeding animals, as well as minimizing the accumulation of fitness-reducing mutations and maintaining genetic diversity. According to the latest estimates, there are at least 30 breeding groups of mini-pigs systematically used as laboratory animals in the world. Among them, there are both breed formations represented by several colonies, and breeding groups consisting of a single herd. It was shown that the main selection strategy is selection for the live weight of adults of 50–80 kg and the adaptation of animals to a specific type of biomedical experiments. For its implementation in the breeding of foreign mini-pigs, selection by live weight is practiced at 140- and 154-day-old age. It was indicated that different herds of mini-pigs have their own breeding methods to counteract inbred depression and maintain genetic diversity. Examples are the maximization of coat color phenotypes, the cyclical system of matching parent pairs, and the structuring of herds into subpopulations. In addition, in the breeding of foreign mini-pigs, molecular genetic methods are used to monitor heterozygosity. Every effort is made to keep the number of inbred crosses in the breeding of laboratory mini-pigs to a minimum, which is not always possible due to their small number. It is estimated that to avoid close inbreeding, the number of breeding groups should be at least 28 individuals, including boars of at least 4 genealogical lines and at least 4 families of sows. The accumulation of genetic cargo in herds of mini-pigs takes place, but the harmful effect is rather the result of erroneous decisions of breeders. Despite the fact that when breeding a number of mini-pigs, the goal was to complete the herds with exclusively white animals, in most breeding groups there is a polymorphism in the phenotype of the coat color.